2013
DOI: 10.1084/jem.20122337
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling RARA transcriptional activation and degradation clarifies the bases for APL response to therapies

Abstract: In PML/RARA-driven acute promyelocytic leukemia (APL), retinoic acid (RA) induces leukemia cell differentiation and transiently clears the disease. Molecularly, RA activates PML/RARA-dependent transcription and also initiates its proteasome-mediated degradation. In contrast, arsenic, the other potent anti-APL therapy, only induces PML/RARA degradation by specifically targeting its PML moiety. The respective contributions of RA-triggered transcriptional activation and proteolysis to clinical response remain dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 31 publications
(45 reference statements)
7
80
0
Order By: Relevance
“…15,30,31 The results obtained here with NPM1 mutant AML unexpectedly bear some similarities with APL. First, mutant NPM1 is degraded with RA or arsenic exposure, and p53 signaling is activated.…”
Section: Discussionsupporting
confidence: 63%
“…15,30,31 The results obtained here with NPM1 mutant AML unexpectedly bear some similarities with APL. First, mutant NPM1 is degraded with RA or arsenic exposure, and p53 signaling is activated.…”
Section: Discussionsupporting
confidence: 63%
“…In our present study, TBLR1-RARa could increase the sensitivity of U937 and HL-60 cells to ATRA and induce a dose-and time-dependent cell differentiation, which was consistent with previous luciferase assays. Besides mediating the degradation of corepressors, TBLR1-RARa was found to be degraded as PML-RARa 47 and homodimerization of TBLR1-RARa were interfered with in the presence of ATRA, which was also responsible for transactivation and cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This actually explained why RA and arsenic antagonize each other for differentiation (Shao et al 1998), but sharply synergize for APL eradication in vivo (Lallemand-Breitenbach et al 1999;Rego et al 2000). The second essential step was the realization that differentiation is linked to transcriptional activation (or derepression), although loss of self-renewal is the direct consequence of PML/RARA loss Ablain et al 2013). Subsequent studies indeed revealed that therapy-induced PML/RARA degradation triggers a p53 response.…”
Section: P53 a Key Effector Of Apl Therapiesmentioning
confidence: 99%
“…these two otherwise unrelated agents. Studies performed in mouse models of APL have conclusively shown that PML/RARA loss is responsible for the abrogation of APL self-renewal Ablain et al 2013Ablain et al , 2014. Subsequent studies showed that PML/RARA loss is actually sufficient for differentiation, thus explaining in vivo myeloid maturation on arsenic exposure (Vitaliano-Prunier et al 2014).…”
Section: Acute Promyelocytic Leukemiamentioning
confidence: 99%